Cesarean section and placental disorders in subsequent pregnancies--a meta-analysis - Klar, Maximilian; Michels, Karin B (Journal of perinatal medicine, 2014)
Despite an increase in the number of cesarean deliveries conducted worldwide, meta-analyses on the long-term effect of cesarean section (CS) on subsequent placental disorders are sparse. To examine the association between CS and three major types of placental disorders (placental abruption, placenta previa, and placenta accreta with its variants increta/percreta) in subsequent pregnancies. We followed the MOOSE consensus statement for meta-analyses of observational studies and searched the PubMed database for observational studies published between January 1990 and July 2011 for examining the association between CS and placental disorders in subsequent pregnancies, without focusing on the effect of increasing number of CSs. We included studies which provided adjusted measures of association for multiparous singleton-pregnant women with one of the three outcomes and information about prior mode of delivery. Five cohort and 11 case-control studies met the inclusion criteria for this meta-analysis. We combined the results of the included cohort and case-control studies as no significant heterogeneity was found across the studies. The calculated summary odds ratio was 1.47 (95% confidence interval, CI: 1.44-1.51) for placenta previa, 1.96 (95% CI: 1.41-2.74) for placenta accreta, and 1.38 (95% CI: 1.35-1.41) for placental abruption. In this meta-analysis, cesarean delivery appeared as a consistently reported risk factor for all three major forms of placental disorders in subsequent pregnancies.